Forage accumulation, chemical composition and morphogenesis of Megathyrsus maximus cv. Quênia under intermittent defoliation - Costa, Newton; Costa , Newton de Lucena; Jank , Liana; Magalhães, João Avelar; Bendahan , Amaury Burlamaqui; Fogaça, Fabíola Helena dos Santos; Rodrigues, Braz Henrique Nunes; Santos, Francisco José de Seixas (Pubvet, 2019)
The effects of pasture rest period (14, 21, 28, 35 and 42 days) on green dry matter (GDM) yield, chemical composition and morphogenetic and structural characteristics of Megathyrsus maximus cv. Quênia were evaluated under natural field conditions. The decrease of rest period resulted in higher GDM yields, however implied significant decreases in the levels of nitrogen, phosphorus, calcium, magnesium and potassium. The leaf appearance rate and populational tiller density are inversely proportional to rest period, occurring the inverse for foliar senescence rate. Maximum GDM yields, number of leaves tiller-1, average leaf length, leaf expansion rate and leaf area index were obtained with rest periods of 36.3; 32.1; 38.0; 24.4 and 34.4 days, respectively. These data suggest that pasture grass grazing at 35 days of rest period were optimal for obtain maximum yields and regrowth of rich forage.
Keywords: chemical composition; dry matter; leaves; tillering; senescence